EUPHEMISM AND GENDER: THE EUPHEMISM USED BY MALE AND FEMALE IN MINANGKABAU SONGS - Ali Habibi; Rizqy Khairuna (Universitas Islam Sumatera Utara (UISU), 2018)
This study aims to identify the differences types of euphemism as an expression in deriving meaning used by the composer of male and female Minangkabau in their song lyrics. The subjects of this research are male and female Minangkabau composers. Data taken from this study were downloaded from youtube and transcribed. The procedure of collecting the data was taken from two of song lyrics by the composers Ipank and Ria Amelia “Rantau Den Pajauh” and “Harok di Rantau urang”. The procedure of analyzing the data was descriptive qualitative method, by having the lyrics identified and underlined to get the types of euphemism that used in their lyrics. The result of analyzing the data indicated that there were three types of euphemism used by male and female composers. The female composer used euphemism more than the male composer. The female composer used three types of euphemism such as ; Circumlocution, Metaphor, understatement and Hyperbole while the male composer only used Hyperbole in the Lyrics.